PERSPEKTIF HUKUM ISLAM MENGENAI PRAKTIK GHARAR DALAM TRANSAKSI PERBANKAN SYARIAH: Indonesia - Hadist Shohih; Ro’fah Setyowati (Faculty of Law, Maranatha Christian University, 2021)
The industrial era 4.0 has presented sophisticated online transactions, this has also brought changes to the banking and investment sector in Indonesia. The phenomenon of online transactions in banking and investment practices has made Islamic finance, which prohibits the concept of giving interest or usury, becomes